Effectiveness of Internship Programs in the World of Work - Kusnadi, Kusnadi; Pramono, Suwito Eko; Hidayah, Isti (Universitas Negeri Semarang, 2024)
The aim of this research is to find out about the existence of internship participants and the effectiveness of activities in accordance with the objectives of the internship, where the government agency, Harbor Master's Office, and Tanjung Emas Port Authority are not places of education. Both facilities and infrastructure are not places of education, so the researcher finds out about the effectiveness and success of the activity and can create new knowledge for the interns in the activity as proven by an assessment at the beginning and end of the activity. The research results show that the internship program significantly contributes to improving the technical skills of interns. Respondents reported increased understanding of the business world of industry (DUDI), the ability to use relevant tools and technology, and the application of academic theory in practical contexts. Apart from that, internship programs also help in developing non-technical skills such as communication, teamwork, and time management. Most students feel better prepared to enter the world of work after completing an internship program. However, this research also identified several challenges faced in implementing the internship program, such as a lack of support from the internship company and limitations in the assignments given to students. Therefore, it is recommended that there be increased collaboration between educational institutions and industry to ensure internship programs that are more structured and beneficial for students.